Diabetes services in the UK: third national survey confirms continuing deficiencies. Issue 1 (1st January 2003) - Jefferson, I G; Swift, P G F; Skinner, T C; Hood, G K
Abstract : Aims: To determine the current level of diabetes services and to compare the results with previous national surveys. Methods: A questionnaire was mailed to all paediatricians in the UK identified as providing care for children with diabetes aged under 16 years. Information was sought on staffing, personnel, clinic size, facilities, and patterns of care. Responses were compared with results of two previous national surveys. Results: Replies were received from 244 consultant paediatricians caring for an estimated 17 192 children. A further 2234 children were identified as being cared for by other consultants who did not contribute to the survey. Of 244 consultants, 78% expressed a special interest in diabetes and 91% saw children in a designated diabetic clinic. In 93% of the clinics there was a specialist nurse (44% were not trained to care for children; 47% had nurse:patient ratio >1:100), 65% a paediatric dietitian, and in 25% some form of specialist psychology or counselling available. Glycated haemoglobin was measured routinely at clinics in 88%, retinopathy screening was performed in 87%, and microalbuminuria measured in 66%. Only 34% consultants used a computer database. There were significant differences between the services provided by paediatricians expressing a special interest in diabetes compared with "non-specialists", the latter describing less frequent clinic attendance of dietitians or psychologists, less usage of glycated haemoglobin measurements, and less screening for vascular complications. Non-specialist clinics met significantly fewer of the recommendations of good practice described by Diabetes UK. Conclusions: The survey shows improvements in services provided for children with diabetes, but serious deficiencies remain. There is a shortage of diabetes specialist nurses trained to care for children and paediatric dietitians, and a major shortfall in the provision of psychology/counselling services. The services described confirm the need for more consultant paediatricians to receive specialist training and to develop expertise and experience in childhood diabetes.